Simple method for the preparation of ultra-small palladium nanoparticles and their utilization for the hydrogenation of terminal alkyne groups to alkanes - Seth, Jhumur; Kona, Chandrababu Naidu; Das, Shyamsundar; Bhagavatula L. V. Prasad (Nanoscale, 2015)
A simple and convenient method for the preparation of ultra-small palladium nanoparticles (Pd-NPs) by a modified digestive ripening method is described. These nanoparticles catalyse the hydrogenation of the terminal alkyne groups to alkanes selectively, and show no effect on other labile protecting and internal alkyne or internal/external alkene groups present in the molecule.